Patient participation in inpatient ward rounds on acute inpatient medical wards: a descriptive study - Redley, Bernice (BMJ Qual Saf, 2019)
BACKGROUND: Meaningful partnering with patients is advocated to enhance care delivery. Little is known about how this is operationalised at the point of care during hospital ward rounds, where decision-making concerning patient care frequently occurs. OBJECTIVE: Describe participation of patients, with differing preferences for participation, during ward rounds in acute medical inpatient services. METHODS: Naturalistic, multimethod design. Data were collected using surveys and observations of ward rounds at two hospitals in Melbourne, Australia. Using convenience sampling, a stratified sample of acute general medical patients were recruited. Prior to observation and interview, patient responses to the Control Preference Scale were used to stratify them into three groups representing diverse participation preferences: active control where the patient makes decisions; shared control where the patient prefers to make decisions jointly with clinicians; and passive control where the patient prefers clinicians make decisions. RESULTS: Of the 52 patients observed over 133 ward rounds, 30.8% (n=16) reported an active control preference for participation in decision-making during ward rounds, 25% (n=13) expressed shared control preference and 44.2% (n=23) expressed low control preference. Patients’ participation was observed in 75% (n=85) of ward rounds, but few rounds (18%, n=20) involved patient contribution to decisions about their care. Clinicians prompted patient participation in 54% of rounds; and in 15% patients initiated their own participation. Thematic analysis of qualitative observation and patient interview data revealed two themes, supporting patient capability and clinician-led opportunity, that contributed to patient participation or non-participation in ward rounds. CONCLUSIONS: Participation in ward rounds was similar for patients irrespective of control preference. This study demonstrates the need to better understand clinician roles in supporting strategies that promote patient participation in day-to-day hospital care.